The Influence of Corporate Social Responsibility on Competitive Advantage: Evidence from the Manufacturing Industry in Kathmandu Valley - Tamang, Jeeban; Uprety, Pravat (Journal of Business and Social Sciences Research, 2025)
The purpose of this study is to examine the influence of corporate social responsibility on competitive advantages in the manufacturing industry, along with the mediating roles of dynamic capabilities and responsible innovation. By employing a convenience sampling technique, data were gathered from a sample of 215 respondents (i.e., factory managers, production engineers, and others) working in the manufacturing companies located in the Kathmandu Valley. The study found that corporate social responsibility (CSR) practices significantly enhance competitive advantage by improving reputation, strengthening stakeholder engagement, and supporting financial performance. It also confirmed positive relationships among CSR, dynamic capabilities (DC), responsible innovation (RI), and competitive advantage (CA). Overall, the findings suggest that ethical conduct, stronger stakeholder ties, and innovation help organisations achieve long-term competitive benefits. The study further recommends that regulators promote CSR initiatives-such as community development, employee welfare, and environmental protection-through incentives like tax benefits, subsidies for sustainable technologies, and recognition programmes.